Precise position control of a helical magnetic robot in pulsatile flow using the rotating frequency of the external magnetic field - Jongyul Kim; Jaekwang Nam; Wonseo Lee; Bongjun Jang; Gunhee Jang (AIP Advances, 2017)
We propose a position control method for a helical magnetic robot (HMR) that uses the rotating frequency of the external rotating magnetic field (ERMF) to minimize the position fluctuation of the HMR caused by pulsatile flow in human blood vessels. We prototyped the HMR and conducted several experiments in pseudo blood vessel environments with a peristaltic pump. We experimentally obtained the relation between the flow rate and the rotating frequency of the ERMF required to make the HMR stationary in a given pulsatile flow. Then we approximated the pulsatile flow by Fourier series and applied the required ERMF rotating frequency to the HMR in real time. Our proposed position control method drastically reduced the position fluctuation of the HMR under pulsatile flow.